Simulasi Potensi Gerakan Tanah Lereng Alami Akibat Perubahan Pola Hujan Wilayah Kecamatan Cimenyan, Kabupaten Bandung, Provinsi Jawa Barat - Rakhman Yuda Prawira; Yunus Ashari; Dono Guntoro (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Landslide is one of the natural disasters that often occur in Indonesia. Lately, landslides have become more frequent and have resulted in fatalities. The landslide disaster itself is one of the geological aspects of the disaster which if it occurs it will be difficult to predict where and when the location of the landslide disaster will be. Cimenyan is one of the sub-districts that has relief units from topography with gentle slopes to steep mountains incised with slope percent ranging from 3% to 140%. The sub-district also has a rainfall of 1500 to 2500 mm per year, with this condition. In the calculation of the safety factor in case 5, it is found that areas that have the potential for ground motion are in cell (M,10) with an FK value of 1,235, cell (P,4) with an FK value of 1,199, cell (P,5) with an FK value of 1 .07, cell (Q,4) with FK value 1.223, and in cell (Q,5) with FK value 1.245. This value is then overlaid on the Cimenyan 2020 land cover map, but only in cells (M,10) Abstrak. Bencana tanah longsor/gerakan tanah merupakan salah satu bencana alam yang sering terjadi di Indonesia. Cimenyan merupakan salah satu kecamatan yang memiliki unit relief dari topografi dengan lereng landai hingga bergunung curam tertoreh dengan persen kemiringan lereng berkisar 3% s/d 140 %. Kecamatan tersebut juga memiliki curah 1500 s/d 2500 mm per tahun, dengan keadaan tersebut tidak menutup kemungkinan Kecamatan Cimenyan akan mengalami kondisi pergerakan tanah. Pada hasil perhitungan faktor keamanan pada case 5 didapatkan daerah yang memiliki potensi terjadinya gerakan tanah yakni pada cell (M,10) dengan nilai FK 1,235, cell (P,4) dengan nilai FK 1,199, cell (P,5) dengan nilai FK 1,07, cell (Q,4) dengan nilai FK 1,223, dan pada cell (Q,5) dengan nilai FK 1,245. Nilai tersebut kemudian dilakukan overlay pada peta tutupan lahan Kecamatan Cimenyan 2020, namun hanya pada cell (M,10)